Recent Study on Barker Coded Modulated Thermal Wave Imaging for Defect Detection of Glass Fiber Reinforced Plastic - Md. M. Pasha; B. Suresh; K. Rajesh Babu; Sk. Subhani; G. V. Subbarao (Advanced Aspects of Engineering Research Vol. 8, 2021)
Depending on the thermal inhomogeneity of the constituent material, infrared active thermography provides subsurface specifics of the test item. Novel processing approaches to enhance detectability and excitations enabling depth analysis with constituent band of frequencies are needed for effective analysis of various defects occurring at different depths in realistic objects. This contribution aims to demonstrate the depth analysis offered by phase modulated coded stimulation for infrared imaging, which has been validated using a glass fibre reinforced plastic plate with embedded Teflon inserts. The Experiments showed that using cumulative energy in pulse compression instead of distributed energy in the current phase analysis improved defect detection. In addition to defect shape preservation, it was discovered that correlation-based processing minimised non-uniform radiation/emissivity.